Total synthesis of isofregenedadiol - Kurhade, Suresh E.; Sanchawala, Abbas I.; Ravikumar, Velayutham; Bhuniya, Debnath; Reddy, D. Srinivasa (Organic Letters, 2011)
The first total synthesis of isofregenedadiol, a bicyclic diterpene isolated from H. Viscosum, is reported starting from a D-(-)-pantolactone chiral pool. A one-pot quadruple reaction sequence comprising an enyne ring-closing metathesis/cross-metathesis/Diels-Alder/aromatization for the construction of a target skeleton Is the highlight of the present synthesis.